Horizons: nuclear astrophysics in the 2020s and beyond. (1st November 2022) - Schatz, H; Becerril Reyes, A D; Best, A; Brown, E F; Chatziioannou, K; Chipps, K A; Deibel, C M; Ezzeddine, R; Galloway, D K; Hansen, C J; Herwig, F; Ji, A P; et al.
Abstract: Nuclear astrophysics is a field at the intersection of nuclear physics and astrophysics, which seeks to understand the nuclear engines of astronomical objects and the origin of the chemical elements. This white paper summarizes progress and status of the field, the new open questions that have emerged, and the tremendous scientific opportunities that have opened up with major advances in capabilities across an ever growing number of disciplines and subfields that need to be integrated. We take a holistic view of the field discussing the unique challenges and opportunities in nuclear astrophysics in regards to science, diversity, education, and the interdisciplinarity and breadth of the field. Clearly nuclear astrophysics is a dynamic field with a bright future that is entering a new era of discovery opportunities.